Immune Checkpoint Inhibitor Induced Hepatitis Injury: : Risk Factors, Outcomes, and Impact on Survival (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Haematology; Oncology; Research